Schopenhauer, Wagner y Nietzsche: Philosophical and Musical Approaches - López, José Manuel (Universidad del Zulia, 2020)
AbstractThe following text covers the studies of Aesthetics and Metaphysics. Its fundamental purpose is to expose the approaches and similarities of philosophical and musical terms between German thinkers-musicians Arthur Schopenhauer, Richard Wagner and Friedrich Nietzsche. All three contributed with fundamental ideas to the philosophy of music that changed the way of thinking, understand and interpret Philosophy itself as well as the musical phenomena, proposing new points of view stressed on an artistic-ontological reflection, which has been influential on the field since the beginning of the 20th century until present days.